2020
DOI: 10.2147/jmdh.s284886
|View full text |Cite
|
Sign up to set email alerts
|

<p>Knowledge and Behaviors Toward Health Care for Elderly Patients with Hypertension, and Quality of Life Among Informal Caregivers in Northern Thailand</p>

Abstract: Background: Informal caregivers play an important role in caring for patients with chronic conditions. Little is known about the quality of life among caregivers of patients with chronic illnesses in Thailand. The purpose of this study was to investigate the relationships among knowledge and behaviors toward health care for elderly patients with hypertension, and the quality of life among informal caregivers. Methods: A total of 402 informal caregivers for their elderly co-habitants suffering from hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This is in accordance with previous findings that used the same tool to assess the quality of life of ethnic minority older adults in Thailand’s rural communities. 17 This is similar to the concept of self-perceived health, which is based on a person’s experience and, learning, and is related to self-inflicted illness; it explained that as individual’s age, their physical and cognitive behaviors would be declined. 32 In the process, elders begin to rely on others for help in social and daily activities.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…This is in accordance with previous findings that used the same tool to assess the quality of life of ethnic minority older adults in Thailand’s rural communities. 17 This is similar to the concept of self-perceived health, which is based on a person’s experience and, learning, and is related to self-inflicted illness; it explained that as individual’s age, their physical and cognitive behaviors would be declined. 32 In the process, elders begin to rely on others for help in social and daily activities.…”
Section: Discussionmentioning
confidence: 69%
“…This is consistent with a previous study, which found that ethnic minority groups have a different quality of life. 17 This could also be explained by a higher number of falling incidents among Hmong highlanders. As stated previously, ethnic groups have very unique ways of life, health beliefs, and social and environmental mores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations